The evaluation of antioxidant and antityrosinase efficacy of Carissa carandas fruit extracts and the development of a preliminary skincare product - Nadechanok Jiangseubchatveera, Charinrat Saechan, Nattawut Leelakanok, Arpa Petchsomrit (Journal of Applied Pharmaceutical Science, 2021)
Carissa carandas Linn. was previously reported as organic solvent extracted from the fruit which demonstrated antioxidant activities. This study aimed to determine the antioxidant and antityrosinase efficacy of C. carandas fruit aqueous extract, formulate a toner from the fruit extract, and evaluate the stability of the toner. By using 2-diphenylpicrylhydrazyl assay, the lyophilized fruit extract exhibited antioxidant capacities with the inhibitory concentration (IC50) value of 633.42 ± 0.64 µg/ml. 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging assays showed that the extract contained 19.67 ± 0.07 mg Trolox equivalent antioxidant capacity (TEAC)/g extract and 11.71 ± 0.04 mg ascorbic acid equivalent antioxidant capacity (AEAC)/g extract. The antityrosinase activity of the extract was in a dose-dependent manner with the IC50 value of 3.34 ± 0.16 mg/ml. The toner from the fruit extract was successfully prepared. The toner remained translucent and was still orange-pink after the six cycles of heating–cooling study. The antioxidant capacity was not significantly changed after the light exposure at 25°C, indicating that the toner could be stored at ambient temperature and did not require light protection. These findings show that C. carandas fruit is a source of natural antioxidants and could be a valuable ingredient for the further development of antioxidant skincare products.
Keywords: Carissa carandas, antioxidant activity, antityrosinase activity, toner, stability study.